Germination and rescue in vitro of immature embryos of black cedar (juglans neotropica diels) (2012)
Immature embryos of Juglans neotropica (Juglandaceae) with 16 and 20 weeks of development were aseptically removed from the fruits and placed in different culture media MS (Murashige and Skoog, 1962), WPM (Lloyd and McCown, 1980) y DKW (Driver and Kuniyuki, 1984) without growth regulators for 60 days. It was observed that embryos with 16 weeks of development did not germinate in any of the three culture media. The embryos with 20 weeks of development germinated 100% in the three culture media. It was found a marked effect of the culture media on the growth of the embryos, the MS medium was significantly better than the DKW and WPM medium (P and lt; 0.05), due to the fact that in MS medium embryos had the highest height and a better proportion of stem/root to obtain complete plantlets. After this, seedlings were adapted to environmental conditions (greenhouse).